Analysing industry clustering to develop competitive advantage for Wualai silver handicraft - Khanita Tumphasuwan (2018)
© Springer-Verlag Berlin Heidelberg 2015. The Wualai community of Northern Thailand represents important intellectual and social capital and their silver handicraft products are desirable tourist souvenirs within Chiang Mai Province. This community has been in danger of losing this social and intellectual capital due to apply an improper tool, the Scottish Enterprise model of clustering. This research aims to analyse and increase its competitive advantages for preventing the loss of social and intellectual capital. To improve the Wualai’s competitive advantage, analysis is undertaken using a Porterian cluster approach, including the diamond model, five forces model and cluster mapping. Research results suggest that utilizing the community’s Buddhist beliefs can foster collaboration between community members and is the only way to improve cluster effectiveness, increase competitive advantage, and in turn conserve the Wualai community.